If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3y + -4(6x + -7y) = 0 6x + 3y + (6x * -4 + -7y * -4) = 0 6x + 3y + (-24x + 28y) = 0 Reorder the terms: 6x + -24x + 3y + 28y = 0 Combine like terms: 6x + -24x = -18x -18x + 3y + 28y = 0 Combine like terms: 3y + 28y = 31y -18x + 31y = 0 Solving -18x + 31y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-31y' to each side of the equation. -18x + 31y + -31y = 0 + -31y Combine like terms: 31y + -31y = 0 -18x + 0 = 0 + -31y -18x = 0 + -31y Remove the zero: -18x = -31y Divide each side by '-18'. x = 1.722222222y Simplifying x = 1.722222222y
| 63/5-21/4 | | -6z/8+7/8=6z/5-11/5-2z/3 | | 7/3x+1/3x=2x+3/3+5/3x | | x^3+2x^2+8x+8=0 | | 2x/3-2/3=-7x/2+4x/3 | | 15.96+2s=T | | y=-3x-69 | | (x+10)/2=7(x-1) | | T=2s+25.96 | | x+2y=-18 | | .5q=315 | | -2=-2(3x-5) | | 1.9y-1.6y= | | -2x-3y=1 | | 5q=315 | | y^11+6=-7 | | 2+2x=4x-8 | | -4x-12y=36 | | y^3+5=-7 | | -16t^2-11t+150=0 | | 3x-12y=27 | | -5(-3q+11)+4(-1-5q)= | | -8p-2p=3+1-6p-5p | | 9n^2-3n=2 | | 3y+3x=36 | | 64n^2=49 | | 5n^2=20n | | 5x^2-1=3 | | 6n^3-22n^2=3n-11 | | -8x+7x=9 | | 2x-3y=-18 | | 27s^7/49s*21s^6/243s |